Mesoscopic structure features in synthetic graphite. (15th March 2018) - März, Benjamin; Jolley, Kenny; Marrow, Thomas James; Zhou, Zhaoxia; Heggie, Malcolm; Smith, Roger; Wu, Houzheng
Abstract: The mesocopic structure features in the coke fillers and binding carbon regions of a synthetic graphite grade have been examined by high resolution transmission electron microscopy (TEM) and Raman spectroscopy. Within the fillers, the three-dimensional structure is composed of crystal laminae with the basal plane dimensions (La ) of hundreds nanometres, and thicknesses (Lc ) of tens of nanometres. These laminae have a nearly perfect graphite structure with almost parallel c-axes, but their a–b planes are orientated randomly to form a " crazy paving " structure. A similar structure exists in the binding carbon regions, with a smaller La . Significantly bent laminae are widely seen in quinoline insoluble inclusions and the graphite regions developed around them. The La values measured by TEM are consistent with estimates from the intensity ratios of the D to G Raman peak in these regions. Atomistic modelling finds that the lowest energy interfaces in the crazy paving structure comprise 5, 6 and 7 member carbon rings. The bent laminae tend to maintain the 6 member rings, but are strained elastically. We suggest that a 7 member carbon ring leaves a cavity representing an arm-chair graphite edge contributing to the Raman spectra D peak. Graphical abstract: Unlabelled Image Highlights: Isostatically moulded graphite shows a structure characteristic of laminae, or "crazy paving", instead of "turbostratic". The lamina dimensions along the basal planes, are generally much larger in the coke filler than those in binding carbon. Atomistic modelling shows that the prismatic boundaries are composed of 5, 6 and 7 member carbon rings.